Clinical and functional analyses of the novel STAR c.558C>A in a patient with classic lipoid congenital adrenal hyperplasia - Liu, Jie; Dai, Hong-Mei; Guang, Gao-Peng; Hu, Wen-Mu; Jin, Ping (Frontiers in Genetics, 2023)
Abstract Objective: Congenital lipid adrenal hyperplasia (LCAH) is the rarest and most serious type of congenital adrenal hyperplasia caused by steroid-based acute regulatory (STAR) protein mutations. Herein, we report compound heterozygous mutations c.558C>A (p.S186R) and c.772C>T (p.Q258*) in a newborn 46 XY patient diagnosed with classic LCAH and explore its clinical and functional characteristics. Methods: Peripheral blood samples were collected from LCAH patient and their families. The pathogenic variant identified by whole-exome sequencing was further confirmed by Sanger sequencing and pedigree verification. The functional consequence and the ability to convert cholesterol into progesterone of the identified STAR Q258* and S186R mutation was analyzed by cell transfection and in vitro assays. Results: The proband presented with severe glucocorticoid and mineralocorticoid deficiency, high adrenocorticotropic hormone, and enlarged adrenals. The heterozygous mutations p.S186R and p.Q258* in the STAR gene were identified in the patient, and her parents were carriers, which is consistent with the autosomal recessive disorder. The STAR p.Q258* mutation has been reported and confirmed to generate a truncated protein. The p.S186R mutation is a novel variant and disrupts the STAR protein. The residual STAR activities of the p.S186R, p.Q258*, and p.S186R/p.Q258* were 13.9%, 7.3%, and 11.2% of the wild type, which proves the main negative effects of mutant proteins. Conclusion: Our findings reveal the molecular mechanisms underlying the pathogenesis of LCAH, further expanding the genotype and clinical spectrum of LCAH.